An analysis of the factors determining compliance behavior of business zakat among owners of SMEs in Selangor / Mohd Rahim Khamis - Khamis, Mohd Rahim (Institute of Graduate Studies, UiTM, 2014)
The total number of business zakat payers among Muslim business entrepreneurs is still small despite numerous efforts undertaken by the zakat authorities and the government to encourage Muslim entrepreneurs to pay business zakat. This has been the subject of much research and investigation in recent years and has led to the issue of compliance behavior of business zakat among Muslim entrepreneurs. Specifically, the small number of payers impacts the collection of zakat on business since business zakat has a huge potential as the main contributor in the total zakat collection. As such, the overall aim of this study is to analyze the factors determining compliance behavior of business zakat among owners of SMEs in Selangor. The analysis covers the measurement of the factors determining compliance behavior and the relationships between these determinant factors (religious practices, level of knowledge, length of business operation, organizational factors, government incentives, law enforcement and business profile i.e. business location and business category) with compliance behavior of business zakat. To this end, data collected from the 276 SMEs entrepreneurs was analyzed through two statistical methods; Rasch Measurement Model and logistic regression analysis.